Porous Ionic Membrane Based Flexible Humidity Sensor and its Multifunctional Applications - Li, Tie (2017)
A highly flexible porous ionic membrane (PIM) is fabricated from a polyvinyl alcohol/KOH polymer gel electrolyte, showing well-defined 3D porous structure. The conductance of the PIM changes more than 70 times as the relative humidity (RH) increases from 10.89% to 81.75% with fast and reversible response at room temperature. In addition, the PIM-based sensor is insensitive to temperature (0–95 °C) and pressure (0–6.8 kPa) change, which indicates that it can be used as highly selective flexible humidity sensor. A noncontact switch system containing PIM-based sensor is assembled, and results show that the switch responds favorably to RH change caused by an approaching finger. Moreover, an attachable smart label using PIM-based sensor is explored to measure the water contents of human skin, which shows a great linear relationship between the sensitivity of the sensor and the facial water contents measured by a commercial reference device.